STUDI SISTEM PENTANAHAN SALURAN UDARA TEGANGAN TINGGI(SUTT) PENGHANTAR 150 KV LUBUK LINGGAU - PEKALONGAN PT. PLN (PERSERO) UNIT PEMBANGKIT DAN TRAMSISI (UPT) BENGKULU - Putra, Dian Eka; Angga, Fitra (JURNAL SURYA ENERGY, 2018)
High-voltage 150 kV air ducts that use open wire are very likely to cause interference, both external and internal interference. And one of the most common disorders is due to lightning strikes. To optimize the distribution of electrical energy in the high voltage air duct, an earth system is installed at the foot of the tower. This study was conducted to calculate the value of foot tower resistance installed on 150 kV high voltage air line  Lubuk Linggau - Pekalongan. Here it will also be discussed to minimize the resistance in earth that exceeds the set standard. Based on measurements using earth tester obtained several towers have a resistance value exceeding the standard on Tower T.20 of 14.5 ohms, Tower T.53 of 12.43 Ohm and Tower T.151 10.33 ohms. After adding the electrode rod obtained by T.20 to 8.056 ohm, T.53 became 8.055 ohms, T.151 8.51 ohms. Of the total 150 kV high voltage  air ducts in Lubuk Linggau - Pekalongan, the grounding system is still good and capable of flowing the fault current to the ground